Isolated pancreatic hyadatidosis - Suman, Sumit Kumar; Gowda H. S., Dharshan; Kumar, P. Shravan; Katepally, Sai Krishna; Gaurav, Anamika (International Journal of Research in Medical Sciences, 2024)
Pancreatic hydatidosis is a rare infection with a frequency of less than one percent. Most of the abdominal hydatid cysts occur in liver. The purpose of this study was to present our experience of few rare cases of isolated pancreatic hydatid cyst, its presentation and management. Five pancreatic hydatidosis patients admitted in Gandhi Medical College, Secunderabad between 2021 to 2023 were reviewed. Demographic characteristics, clinical findings, and laboratory data were collected. Commonest symptom was pain in left upper quadrant followed by jaundice. The preoperative diagnosis was established in 3 patients by combination of ultrasonography, computed tomography, endoscopic ultrasonography and serological tests. Surgical treatment was done in three cases and two were medically treated. None of them had recurrence during a follow-up of 1 year. Pancreatic hydatid cyst even if rare should be considered in any pancreatic cystic mass in endemic countries like India.